“Faktor-Faktor yang Berpengaruh Terhadap Ketepatan Waktu Pelaporan Keuangan pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2013-2016” - Anindya Setyaningrum, 14.05.52.0166; Widiatmoko, Jacobus (Students' Journal of Accounting and Banking, 2018)
This study examines the effect of profitability, debt to equity ratio, firm size, and firm age on manufacturing company listed in Indonesia Stock Exchange. This study used purposive sampling method in sample selection, the criteria for a sample is manufacturing company listed in Indonesia Stock exchange during the period from 2013 to 2016. Based on the criteria, obtained a sample of 449 companies over a four-year observation period. Relationship and (or) influence between variable is described by using logistic regression analysis. The result showed that debt to equity ratio variable has negative effect significant to the timeliness of financial report, firm age variable had positive effect significant to the timeliness of financial report. Profitability and firm size variable has positive effect not significant to the timeliness of financial report. Keyword: timeliness, profitability, debt to equality ratio, firm size, and firm age